Use of Androcoll-ETM to Separate Frozen-Thawed Llama Sperm From Seminal Plasma and Diluent - Guillén Palomino, Crissthel Yverlin; Fumuso, Fernanda Gabriela; Bertuzzi, Mariana Lucía; Giuliano, Susana María; Velásquez González, Nicolás; Bariani, Maria Victoria; Carretero, María Ignacia (Frontiers in Veterinary Science, 2021)
It is not easy to separate frozen-thawed South American Camelid sperm from seminal plasma (SP) and diluents to be used for in vitro embryo production. The objective of this study was to evaluate Androcoll-ETM (AE) efficiency to separate llama sperm from SP and freezing extender in frozen-thawed semen. A total of 22 ejaculates from 5 Lama glama males were collected using electroejaculation. After performing semen analysis (sperm motility, concentration, viability, membrane function and acrosome integrity), samples were cryopreserved with a diluent containing lactose, EDTA, egg yolk and 7% of dimethylformamide. After thawing, samples were divided in aliquots, one of which was used as a control and the others processed by AE. Experiment 1 (12 ejaculates): 100 µl of frozen-thawed semen were placed on top of 1000 µl AE column and centrifuged at 800 g for 10 min. Experiment 2 (10 ejaculates): two samples of 100 µl of frozen-thawed semen were placed on two columns of 500 µl AE each, and both were centrifuged at 800 g for 10 and 20 min, respectively. Pellets were resuspended in TALP medium and sperm parameters were evaluated. A significant decrease in all sperm parameters was observed in thawed samples compared to raw semen. AE allowed the separation of frozen-thawed sperm from SP and freezing extender, independently from the height of the column used and time of centrifugation assayed. Although no significant differences were found between AE columns, higher sperm recovery was observed with 500 µl of AE coupled with 20 min of centrifugation. Despite the significant decrease observed in sperm motility in AE samples, no changes in sperm viability, membrane function and acrosome integrity were observed when comparing control thawed semen with the sperm recovered after AE (p > 0.05). Conclusion: the use of Androcoll-ETM columns, either 500 or 1000 µl, allows the separation of frozen-thawed llama sperm from SP and freezing extender, preserving the viability, membrane function and acrosome integrity. Of the protocols studied, 800 g centrifugation during 20 min using a 500 µl column of AE would be the method of choice to process frozen-thawed llama semen destined for reproductive biotechnologies.